Immunoglobulins and EB virus antibodies in infectious mononucleosis - Sutton, R. N. P. (1973)
Antibodies to EB virus capsid, EB virus complement-fixing antibodies and IgM, IgA and IgG immunoglobulins were estimated in sera from seventy-four patients with infectious mononucleosis, eighty-nine control patients (mostly with infectious diseases) and 232 healthy medical students and nurses. Complement fixing (but not virus capsid) antibodies were much lower in patients tested during active infectious mononucleosis than in patients tested during late convalescence or in controls, a disparity which could form the basis of a diagnostic test. Immunoglobulin levels were higher in patients with active infectious mononucleosis than in controls and, when tested 6 months to 2 yr later, were still higher than those in healthy individuals.